Forged in Suffering: The Birth of Dystopian Imagination in Arabic Literature: Case Studies from Utopia, The Queue, and Utared - Al-Khamisi, Fatima (International Journal of Language and Literary Studies, 2025)
This study examines the rise of dystopian imagination in modern Arabic literature through three novels: Utopia (Towfik, 2008), The Queue (Abdel Aziz, 2016), and Otared (Rabie, 2016). Using close textual analysis within a comparative literary framework, it identifies a three-part pattern of suffering, i.e., material deprivation (Utopia), temporal suspension (The Queue), and bodily collapse (Otared). Unlike Western dystopias that focus on technological speculation or ideological control, these works emphasize lived realities, making structural, bureaucratic, and physical suffering central to their aesthetic and political messages. The novels act as testimonies, giving voice to marginalized experiences and transforming everyday suffering into ethical and narrative engagement. The study also suggests expanding the collection of Arabic dystopias, situating them within global and postcolonial debates, and incorporating them into world literature courses. By doing so, it examines how Arabic literature reconfigures the dystopian imagination through representations of human suffering, thereby contesting Eurocentric conceptions of the genre.